KONSEKUENSI YURIDIS PROSES PEMUTUSAN HUBUNGAN KERJA TERHADAP PEKERJA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 168/PUU-XXI/2023 - Prasetyo, Kurniadi (Gapenas Publisher, 2025)
The norms of labour law experienced dynamics after the Constitutional Court (MK) issued Decision Number 168/PUU-XXI/2023 which was pronounced in an open Plenary Session of the Constitutional Court on 31 October 2024. In the verdict, among other things, it is stated that in the event that workers/labourers refuse termination of employment (PHK), employers and workers are obliged to conduct bipartite negotiations in a deliberative manner to reach consensus. Furthermore, it is stated that in the event that bipartite negotiations do not reach an agreement, termination of employment can only be carried out after obtaining a determination from an industrial relations dispute resolution institution whose decision has permanent legal force. This research uses a normative legal approach with an emphasis on the inventory of positive law, legal doctrine, and principles. The dynamics that occur and must be considered by employers are that if there is a rejection of layoffs by workers, it is mandatory to conduct bipartite negotiations in deliberation to reach consensus first and employers may not lay off workers before obtaining a determination from the industrial relations dispute resolution institution whose decision has permanent legal force.